The Biocompatibility of Sodium Lauryl Sulphate on _x000D_ Developing Zebrafish Embryos - TAĞTEKİN, DİLEK; MEŞELİ, SİMGE (My University, 2021)
Objective: As an anionic surfactant, sodium lauryl sulphate (SLS), is used as an emulsifying agent in toothpastes as well as many different household cleaning products. Many toothpastes contain SLS and it is responsible for the formation of foam when brushing. However SLS may also irritate sensitive teeth and gums. Lipid peroxidation (LPO) is defined as an autoxidation process that is induced through the attack of free oxygen radicals leading to oxidative stress in the pathophysiology of various diseases. LPO causes the formation of highly reactive products including different aldehydes, ketones, and alkanes serving as biomarkers of LPO. In our study we aimed to expose zebrafish embryos to SLS and determine LPO in SLS exposed zebrafish embryos. Material and Method: Zebrafish embryos that were dividing normally and which had spherical shapes were chosen and they were exposed to SLS both in low and high concentrations in well plates for 72 hours. Rates of mortality and hatching were determined. The levels of malondialdehyde were evaluated using the Yagi's method as the end products of LPO in the form of thiobarbituric acid reactive substances. Results: Our findings showed LPO increased significantly in both low SLS (p<0.05) and high dose SLS (p<0.05) exposed zebrafish embryos when they were compared to the control group. Conclusion: It may be suggested that LPO is an early indicator of exposure to SLS during embryogenesis and further studies are required to confirm this finding.

Amaç: Sodyum lauril sülfat (SLS), ev temizlik ürünleri ve diş macun?larında emülsifiye edici temizlik maddesi olarak kullanılan anyonik _x000D_ bir yüzey aktif maddedir. Birçok diş macunu fırçalarken köpük olu?şumuna yol açan SLS içerir. Ancak SLS hassas diş ve diş etlerini tahriş _x000D_ edebilir. Lipid peroksidasyonu (LPO), çeşitli hastalıkların patofizyo?lojisinde oksidatif strese yol açan serbest radikallerin saldırısı ile _x000D_ başlatılan bir otooksidasyon sürecidir. LPO, LPO'nun biyobelirteçleri _x000D_ olarak görev yapan farklı aldehitler, ketonlar, alkanlar dahil olmak _x000D_ üzere reaktif ürünlerin oluşumuna neden olur. Çalışmamızın amacı, _x000D_ SLS'ye maruz kalan zebra balığı embriyolarında oluşan LPO'yu de?ğerlendirmektir._x000D_ Gereç ve Yöntem: Normal olarak bölünen küresel embriyolar, 72 _x000D_ saat boyunca plaka kuyucuklarında düşük ve yüksek dozda SLS'ye _x000D_ maruz bırakılmıştır. Mortalite ve kuluçkadan çıkma oranları belir?lenmiştir. Tiyobarbitürik asit reaktif maddeler olarak LPO'nun son _x000D_ ürünü olan malondialdehit (MDA) düzeyini belirlemek için Yagi _x000D_ yöntemi kullanılmıştır._x000D_ Bulgular: Bulgularımız, hem düşük SLS (p<0,05) hem de yüksek _x000D_ doz SLS’ye (p<0,05) maruz kalan zebra balığı embriyolarında kont?rol grubu ile karşılaştırıldığında LPO'nun önemli ölçüde arttığını _x000D_ göstermiştir._x000D_ Sonuç: LPO'nun embriyogenez sırasında SLS'ye maruz kalmanın _x000D_ erken bir göstergesi olduğu öne sürülebilir ve bu bulguyu doğru?lamak için farklı çalışmaların yapılması gerektiği düşünülmektedir.
Sodyum Lauril Sülfatın Gelişmekte Olan Zebra Balığı Embriyolarında Biyouyumluluğu